Progressive APOBEC3B mRNA expression in distant breast cancer metastases. - Anieta M Sieuwerts; Willemijne A M E Schrijver; Simone U Dalm; Vanja de Weerd; Cathy B Moelans; Natalie Ter Hoeve; Paul J van Diest; John W M Martens; Carolien H M van Deurzen (PLoS ONE, 2017)
Background APOBEC3B was recently identified as a gain-of-function enzymatic source of mutagenesis, which may offer novel therapeutic options with molecules that specifically target this enzyme. In primary breast cancer, APOBEC3B mRNA is deregulated in a substantial proportion of cases and its expression is associated with poor prognosis. However, its expression in breast cancer metastases, which are the main causes of breast cancer-related death, remained to be elucidated. Patients and methods RNA was isolated from 55 primary breast cancers and paired metastases, including regional lymph node (N = 20) and distant metastases (N = 35). APOBEC3B mRNA levels were measured by RT-qPCR. Expression levels of the primary tumors and corresponding metastases were compared, including subgroup analysis by estrogen receptor (ER/ESR1) status. Results Overall, APOBEC3B mRNA levels of distant metastases were significantly higher as compared to the corresponding primary breast tumor (P = 0.0015), an effect that was not seen for loco-regional lymph node metastases (P = 0.23). Subgroup analysis by ER-status showed that increased APOBEC3B levels in distant metastases were restricted to metastases arising from ER-positive primary breast cancers (P = 0.002). However, regarding ER-negative primary tumors, only loco-regional lymph node metastases showed increased APOBEC3B expression when compared to the corresponding primary tumor (P = 0.028). Conclusion APOBEC3B mRNA levels are significantly higher in breast cancer metastases as compared to the corresponding ER-positive primary tumors. This suggests a potential role for APOBEC3B in luminal breast cancer progression, and consequently, a promising role for anti-APOBEC3B therapies in advanced stages of this frequent form of breast cancer.